2019
DOI: 10.1371/journal.pmed.1002916
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with heart failure outcomes in 11 Asian regions: A cohort study

Abstract: BackgroundAsians are predisposed to a lean heart failure (HF) phenotype. Data on the ‘obesity paradox’, reported in Western populations, are scarce in Asia and have only utilised the traditional classification of body mass index (BMI). We aimed to investigate the association between obesity (defined by BMI and abdominal measures) and HF outcomes in Asia.Methods and findingsUtilising the Asian Sudden Cardiac Death in Heart Failure (ASIAN-HF) registry (11 Asian regions including Taiwan, Hong Kong, China, India, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 28 publications
10
52
0
2
Order By: Relevance
“…Similar results were obtained in patients with heart failure. 30 In these patients, the "obesity paradox" was observed only when defined using BMI, with waist-to-height ratio showing the opposite association with mortality or hospitalization due to heart failure. The authors also observed that "lean-fat patients," with high waist-to-height ratio and low BMI, had the worst outcomes.…”
Section: Elderly: Bmi Does Not Reflect the Same Mortality Risk In Ymentioning
confidence: 86%
“…Similar results were obtained in patients with heart failure. 30 In these patients, the "obesity paradox" was observed only when defined using BMI, with waist-to-height ratio showing the opposite association with mortality or hospitalization due to heart failure. The authors also observed that "lean-fat patients," with high waist-to-height ratio and low BMI, had the worst outcomes.…”
Section: Elderly: Bmi Does Not Reflect the Same Mortality Risk In Ymentioning
confidence: 86%
“…24 Similar findings were reported in studies that used CHD, heart failure, atrial fibrillation, diabetes mellitus, and other disease conditions as outcomes. 6,7,11,14,25 This is likely because BMI being an inaccurate indicator of body fatness. 15 Skinfold thickness may serve as an alternative but its role in clinical practice and research investigation has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, "obesity paradox" has been consistently reported. [11][12][13] One of the essential explanations is that BMI fails to describe body fat distribution as an index of adiposity, 14,15 when studies have emphasized that the accumulation of visceral and ectopic fat is an independent risk marker of cardiovascular and metabolic morbidity and mortality. 2,3 Moreover, visceral and ectopic fat is usually measured by magnetic resonance imaging (MRI) and computerized tomography (CT) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical findings have shown that dysregulation of adipocytokine production is a crucial factor contributing to the manifestation and progression of AO-induced metabolic and CV complications including HF ( 179 , 181 , 185 , 193 , 240 ). The impact of altered adipocytokine profile on CV remodeling in patients with several phenotypes of HF is remarkably variable and does not always relate to inducing inflammatory activation.…”
Section: Adipose Tissue Dysfunction and Heart Failurementioning
confidence: 99%